Diabetes gestacional como factor asociado a policitemia neonatal en el Hospital Distrital “El Esfuerzo” de Florencia de Mora - Albujar Rafaile, Pedro Antonio (2019)
Gestational diabetes is an increasing pathology within the rising trend of diabetes mellitus worldwide; also, neonatal polycythemia can cause deterioration of oxygenation and tissue perfusion, causing variable damage to vital organs of the newborn; previous studies have found varying degrees of interrelation between these pathologies, in other populations. Objective: to determine the association between gestational diabetes and neonatal polycythemia in neonates born in the District Hospital “El Esfuerzo” in Florencia de Mora, in the years 2014 to 2018. Method: observational, analytical, case-control study, retrospective; with evaluation of all the medical records (neonatal and maternal) of the births produced in the period 2014 to 2018 at the District Hospital “El Esfuerzo” of the district of Florencia de Mora, province of Trujillo, region La Libertad.